Ritual dimensions of civil religion - Máté-Tóth András (A vallási kultúrakutatás könyvei, 2014)
The main goal of our paper is to elaborate an adequate framework of interpretation for the public events in contemporary Central and Eastern Europe. In order to achieve this aim, first we will present some typical public events in our region – focusing on Hungary. Afterwards, we offer some possible interpretations, which may supply us with important insights concerning the role of public events in contemporary societies.